ANALYSIS OF APPROACHES TO THE ELECTRICAL ENERGY MANAGEMENT SYSTEM IN MICROGRIDS (Modern education and development, 2025)
Today, based on new principles, the structure that connects the reliable communication between the producer and the consumer, which plays a leading role in the modernization of the entire energy industry in the electric power system, is attached to the power grid.